Dental Health Promotion: A Diet That Supports Dental and Oral Health Through a Family Approach - Haryani, Wiworo (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: choosing the wrong diet and the influence of modern lifestyles can cause dental caries in children, especially the consumption of cariogenic foods. One of the community empowerment efforts is by involving community members who are willing to voluntarily be involved in dental health problems, so that dental health promotion through a family approach can improve community dental health behavior. Objective: to analyze the effectiveness of dental health promotion about eating patterns that support oral and dental health through a family approach to dental health knowledge. Methods: Methods: Pre-experimental research with pretest-posttest one group design. The sampling technique was purposive sampling as many as 50 respondents. The study was conducted at Surokarsan village, Mergangsan, Yogyakarta. The research instrument used a questionnaire and data analysis used the SPSS program with the Paired Sample Test. Results: the level of knowledge of respondents increased by 22.5 and the average value of knowledge before counseling was 57 to 79.50 with a p value of 0.016 Conclusion: Promotion of dental health about eating patterns that support oral and dental health through a family approach is effective in increasing public dental health knowledge .